OP0213 The Degree of Activity Measured with the EULAR-SS Disease Activity Index (ESSDAI) Strongly Correlated with Death in Patients with Primary Sjogren Syndrome (GEAS-SS REGISTRY). (10th June 2014) - Brito Zeron, P.; Retamozo, S.; Solans, R.; Fraile, G.; Morera-Morales, L.; Suárez-Cuervo, C.; Rascόn, F.J.; Qanneta, R.; Pérez-de-Lis, M.; Akasbi, M.; Ripoll, M.; Pinilla, B.; et al.
Abstract : Objectives: To analyse the association between the new 2010 EULAR-SS disease activity index (ESSDAI) and death in a large cohort of Spanish patients with primary Sjogren syndrome (pSS) Methods: The GEAS-SS multicenter registry was formed in 2005 with the aim of collecting a large series of Spanish patients with primary SS. It includes 12 Spanish centers with experience in the management of SS. By November 2013, the database included 921 patients fulfilling the 2002 classification criteria for pSS. The cumulated ESSDAI index (2010 EULAR-SS disease activity index) was retrospectively calculated at diagnosis. Statistical values were expressed as the hazard ratio (HR) and 95% confidence interval (CI) for death. Results: The cohort consisted of 921 patients, including 867 (94%) women with a mean age at diagnosis of 53.81±0.49 years (range, 14-88) and a disease evolution ranging from 6 to 360 months (mean, 74.9±4). 882 (96%) patients presented xerostomia, 878 (95%) xerophtalmia, 805/863 (93%) had positive ocular tests, 598/676 (88%) altered parotid scintigraphy and 424/482 (88%) a salivary gland biopsy showing lymphocytic infiltrates grade 3 or 4. After a mean follow-up of 75 months, 83 (9%) patients died due to causes related to SS (n=27), infections (n=17), cardiovascular disease (n=20) and other causes (n=11); the cause of death was unknown in 8 patients. The active domains (score ≥1) associated with mortality were the constitutional (HR 2.66, CI 1.38-5.11), pulmonary (HR 2.13, CI 1.09-4.16) and biological (HR 3.01, CI 1.91-4.76), with the pulmonary and biological domains being independently associated with death. Specific analysis according to the cause of death showed that activity at the constitutional, lymphadenopathy, hematological and biological domains was a predictive factor of death related to pSS (HR of 6.27, 4.99, 2.59 and 7.88, respectively), while activity at the constitutional, cutaneous, pulmonary, renal neurological and hematological domains predicted mortality related to infection (HR of 4.23, 5.93, 5.93, 9.29, 4.46 and 3.7, respectively). No statistical associations were found between activity of the ESSDAI domains and mortality related to cardiovascular disease or other causes of death. Conclusions: The degree of activity measured in the majority of domains of the new 2010 EULAR-SS disease activity index (ESSDAI) strongly correlated with mortality in a large cohort of Spanish patients with primary SS. Activity of constitutional and lymphadenopathy domains (closely related to lymphoma) correlated with death caused by the SS itself, while activity in the main extraglandular sites of involvement (in which high doses of corticosteroids and immunosuppressive agents are used) correlated principally with death caused by infection. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4342